Parenting skills and family stressors : implications for child removal and maltreatment recidivism among CPS involved families - Dumessa, Lediya A. (2015)
Child maltreatment continues to be a significant problem in the United States. Although afamily’s involvement with Child Protective Services (CPS) may increase the welfare of children,the risk of maltreatment reoccurrence (i.e., recidivism) is common. Moreover, some studies findthat children who have been removed from the home have a higher likelihood of experiencingadditional maltreatment compared to children who remain with their caregivers following asubstantiated case of abuse. This may, in part, be explained by the severity of the index event,but further research is needed to examine parental and family variables that contribute to the riskof being removed (as a proxy for severity) and subsequent maltreatment recidivism. Theproposed study utilized archival data from CPS case files to examine parenting variables,domestic violence, and caregiver unemployment status as predictors of maltreatment severity andrecidivism, respectively. Additional child variables were also be explored in association withthese outcomes. Findings may help inform CPS caseworkers and policy makers of the factorsthat contribute to child outcomes.